THE USE OF PHYSICAL PHENOMENON AS AN INNOVATIVE SOURCE IN ART EDUCATION - Heiba, Eslam; Al- Yahyai, Fakhriya; Mansour, Heba; Al- Amri, Mohammed (PEOPLE: International Journal of Social Sciences, 2019)
It is undoubtable that there is a reciprocity relationship between the different sciences and fields of knowledge. The relation between art and science is one that extends ancient times since both of them use search and experimentation methods in pursuit of reaching the best results and satisfactory solutions which makes them in continuous development. Likewise, Art education draws its references and aesthetic values from all that is found neoteric whether it is in nature, heritage or other sciences. The idea of integration between art and science prompts on finding innovative ways towards creativity, because whenever the sources behind the design were of a scientific nature, the higher the visual connotations are closer to perception and mental receptivity. Hence, researchers are trying to create new experimental approaches through the study and analysis of some physical phenomena, such as energy, frequency and vibration, which produces precise and perfect artistic forms in harmonious rhythms and in accordance with formalized geometric and mathematical relations of scientific origin that can be used by art students to create innovative design works as intellectual starting points, can be consulted and relied on as technical references, with a formal logic, and mental legitimation, which contributes to the enrichment of the aesthetic values ​​of the art work. So, this study aims to take advantage of some physical phenomena such as energy and frequency and vibration and its formal output as an innovative source in teaching arts.